Echographie Pédiatrique En Pratique Hospitaliere Au Centre Hospitalier Universitaire (CHU) De Kara Au Togo - N’timon, B.; Gbande, P.; Dagbe, M.; Dossouvi, T.; Tchaou, M.; Amadou, A.; Sonhaye, L.; Agoda-Koussema, L.K.; Adjenou, K.V. (European Scientific Journal, ESJ, 2018)
Purpose: To list pediatric ultrasound exams performed at Kara University Hospital Center in Togo and the pathologies observed. Materials and methods: This was a retrospective and descriptive study of the results of pediatric ultrasound examinations performed in the Department of Radiology and Imaging of Kara University Hospital Center. The study ran from January 1, 2013 to December 31, 2016, over a period of 3 years. Results: The frequency of pediatric ultrasounds was 5.1%. The average age of the patients was 2.16 years with extremes of 1 day to 15 years. There was a male predominance with a sex ratio of 1.4. Abdomino-pelvic ultrasound were the most represented, 92%, followed by cervical ultrasound in 2.6% of cases. Abdominal ultrasound indications were dominated by abdominal pain in 33.6% of cases, followed by palpation of abdominal mass in 15.7%. Cervical ultrasounds were motivated in 5 out of 8 cases by the cervical swelling. Abdomino-pelvic ultrasonography was pathological in 70.1% of cases. Hepatic affections were the most common abdominal abnormality in 37.8% of cases followed by splenic disorders. Hepatic lesions were dominated by European Scientific Journal February 2018 edition Vol.14, No.6 ISSN: 1857 – 7881 (Print) e - ISSN 1857- 7431 444 homogeneous hepatomegaly with 63.2% of cases. Cervical ultrasound was pathological in 6 out of 8 cases. The lesions observed were mainly cervical lymphadenopathy (4 cases out of 6). Conclusion: Ultrasound is a very useful tool in the exploration of pediatric diseases. The abdominal ultrasound is the most performed and hepatic pathologies are the most common.